ZBTB20 is required for anterior pituitary development and lactotrope specification - Cao, Dongmei (Nat Commun, 2016)
The anterior pituitary harbours five distinct hormone-producing cell types, and their cellular differentiation is a highly regulated and coordinated process. Here we show that ZBTB20 is essential for anterior pituitary development and lactotrope specification in mice. In anterior pituitary, ZBTB20 is highly expressed by all the mature endocrine cell types, and to some less extent by somatolactotropes, the precursors of prolactin (PRL)-producing lactotropes. Disruption of Zbtb20 leads to anterior pituitary hypoplasia, hypopituitary dwarfism and a complete loss of mature lactotropes. In ZBTB20-null mice, although lactotrope lineage commitment is normally initiated, somatolactotropes exhibit profound defects in lineage specification and expansion. Furthermore, endogenous ZBTB20 protein binds to Prl promoter, and its knockdown decreases PRL expression and secretion in a lactotrope cell line MMQ. In addition, ZBTB20 overexpression enhances the transcriptional activity of Prl promoter in vitro. In conclusion, our findings point to ZBTB20 as a critical regulator of anterior pituitary development and lactotrope specification.